Use of social media by parents raising autistic children in East London, Eastern Cape, South Africa - Bikitsha, Tina Sisanda (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
This study investigates how local parents use social media platforms, focusing on the platforms they use, how they access them, the barriers they face, and the effectiveness of social media in supporting them. Using a qualitative approach and informed by the theoretical frameworks of digital divide and digital literacy, semi- structured interviews were conducted with 10 participants (parents and caregivers), the majority of whom resided in an urban area with one from a township. The findings reveal that social media, especially WhatsApp, Facebook, and YouTube, play an important role in providing emotional support, connecting parents with similar challenges, and information sharing. However, the effectiveness of these platforms is restricted by factors such as high data costs, frequent power outages (loadshedding), limited digital literacy, disinformation, and a lack of South Africa-based online autism support groups. Additionally, the research reveals a gender disparity in social media engagement, with fewer fathers joining online support groups. Recommendations include developing relationships with policymakers to reduce data costs and enhance digital access, creating locally appropriate resources and digital literacy initiatives to improve social media accessibility for South African parents and caregivers of autistic children and, addressing the under-representation of male participants. Future research should include recruiting more fathers and caregivers, particularly in low socioeconomic regions like the Eastern Cape, and parents who lack access to social media due to financial and digital literacy challenges, to better understand their use of social media as parents or caregivers raising children with autism. The researcher's own experience as a parent of an autistic child provides a unique perspective, which allows a more empathic and authentic understanding of the experiences of the interviewed parents.
Keywords: Autism spectrum disorders -- South Africa; Autism spectrum disorders in children -- South Africa; Mothers of children with disabilities -- South Africa; Social media -- South Africa East London; Digital divide -- South Africa East London; Digital literacy